التَّشخِيصُ فِي شِعْرِ أَبِي بَكْرٍ بنِ القُوطِيَّةِ الحَفِيدِ مِنْ شُعَرَاءِ القَرْنِ الخَامِسِ الهِجْرِي - مجيد سرحان, أنوار (Al-Adab Journal, 2018)
This paper deals with the study of a technical phenomenon associated Metaphor closely is the Personification (which give human qualities to inanimate objects) in the poetry of the poet Andalusian is Abu Bakr bin Gothic grandson of the poets of the fifth century, we have tried to monitor this phenomenon in his poetry and stand on the dimensions of this phenomenon and its aesthetic and its impact on enrich the poetic text and its impact in the rhetorical beautiful images.